Influence of loop diuretics on denosumab-induced hypocalcaemia in osteoporosis: a retrospective observational analysis - Toshinori Hirai; Yukari Mori; Toru Ogura; Yuki Kondo; Yuka Sakazaki; Yoichi Ishitsuka; Akihiro Sudo; Takuya Iwamoto (BMC, 2024)
Abstract Background We examined whether denosumab-induced hypocalcaemia is evident in osteoporosis when given loop diuretics that promote urinary calcium excretion. Methods Japanese Spontaneous Adverse Drug Event Reports was analyzed to examine signals for denosumab-induced hypocalcaemia co-administered loop diuretics. We retrospectively included osteoporotic patients to detect predictors for denosumab-induced hypocalcaemia (corrected calcium level < 8.5 mg/dL) using multivariate logistic regression analysis. We compared differences in corrected calcium levels (ΔCa = nadir-baseline). Results A significant signal for hypocalcaemia was detected (Reporting odds ratio = 865.8, 95% confidence interval [95% CI]: 596.8 to 1255.9, p < 0.0001). Among 164 patients (hypocalcaemia, 12%), loop diuretics have a significant association with hypocalcaemia (odds ratio [OR] = 6.410, 95% CI: 1.005 to 40.90, p = 0.0494). However, hypocalcaemia was found to be lower in high corrected calcium levels at baseline (OR = 0.032, 95% CI: 0.005 to 0.209, p < 0.0001) and calcium and vitamin D supplementation (OR = 0.285, 95% CI: 0.094 to 0.868, p = 0.0270). In the non-hypocalcaemia, ΔCa decreased significantly in the denosumab plus loop diuretics than in the denosumab alone (-0.9 [-1.3 to -0.7] mg/dL vs. -0.5 [-0.8 to -0.3] mg/dL, p = 0.0156). However, ΔCa remained comparable in the hypocalcaemia despite loop diuretics co-administration (-1.0 [-1.2 to -0.8] mg/dL vs. -0.8 [-1.5 to -0.7] mg/dL, p = 0.7904). Conclusions Loop diuretics may predispose to developing denosumab-induced hypocalcaemia.